Analisando o programa de apoio as incubadoras de cooperativas populares no contexto do debate sobre as políticas sociais no Brasil - Melo, Ícaro Moreno de Souza (2018)
This dissertation aims to analyse the National Program of Incubators of Popular Cooperatives (Proninc, in the portuguese abbreviation) since the debates, in the general and in Brazil, about social policies. For that, we carry out a course seeking to place the patterns of State intervention in the social field and how they vary in the history. The contextualization in the brazilian case is fundamental to recognize the specific chateristics that these initiatives from the public power acquired in that country. Being the program somehow a product of the organization of the political purpose from the social movement of ‘solidarity economy’, it has been necessary also to approach the insertion of the theme in the brazilian State, for better comprehension of the studied object. The author has part of the staff that did the ‘Proninc Evaluation 2017’ what has allowed an experience in seminars and in the field that has contributed in the process of making of this dissertation. In that way, we used the methodologies of sistematization of experiences described by Jara Holliday (2012) and also tried to get closer of the ‘grounded theory’ proposal developed by Flick (2004).